Imaging Manifestations of Soft Tissue Lymphoma - Debi, Uma; Kumar, Maoulik; Singh, Lokesh; Sagar, Sathya; Maralakunte, Muniraju; Bhatia, Vikas; Sinha, Anindita; Devi, Gita; Sandhu, M S (Archives of Clinical and Medical Case Reports, 2020)
Malignant bone lymphomas are a rare disease. According to an initial extent, bone lymphoma can be primary or secondary. Primary lymphoma of bone (PLB) has an overall good prognosis, commonly involves meta-diaphysis of long bones. Secondary osseous lymphoma preferentially involves an axial skeleton. Musculoskeletal lymphoma requires multimodality imaging evaluation by radiograph, CT, MRI, bone scintigraphy, and 18F-FDG PET-CT. Medullary bone lesion without cortical involvement is an important feature of lymphoma and it must be considered as a differential of a permeative bone lesion with soft tissue involvement. Muscular lymphoma does not have characteristic imaging findings. The final diagnosis of musculoskeletal lymphoma requires histopathology analysis.